Graphene premix, coating composition and coated article

Through the combination of graphene premix, glycidyl ether compounds and ionic liquid dispersants, the problem of insufficient compatibility of conductive additives is solved, and high-efficiency and low-cost antistatic coatings are achieved, and graphene is not easily dispersed. Problem, providing uniform appearance and excellent antistatic properties.

CN117946544BActive Publication Date: 2024-12-17SHERWIN-WILLIAMS (NANTONG) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311563297.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-21
Publication Date
2024-12-17
Estimated Expiration
2043-11-21

AI Technical Summary

Technical Problem

The compatibility of conductive additives in existing antistatic coatings is insufficient, resulting in the coating being foamed and powdered, and the cost is high, limiting its application range.

Method used

Using graphene premix, containing a dispersant with a sulfonimide moiety and a glycidyl ether compound, forms a coating composition with easy dispersion and excellent antistatic properties, and improves the dispersion of graphene through ionic liquid dispersants and Antistatic properties.

Benefits of technology

A uniform mixing of graphene and coating composition without ultrasound or grinding is achieved, providing a uniform appearance and improved antistatic properties, reducing costs and overcoming the problem of graphene not being easily dispersed.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to a graphene premix, a coating composition and a coated product. The graphene premix of the present application comprises: at least one dispersant having a sulfonimide moiety, at least one glycidyl ether compound, and at least one graphene. The present application also provides a coating composition comprising the graphene premix, and a coated product comprising a coating formed by the coating composition. The graphene premix of the present application can be quickly and uniformly mixed with other components of the coating composition without the need for dispersing means such as ultrasound or grinding. The graphene premix and coating composition of the present application have excellent antistatic properties, and have the advantages of low cost and easy dispersion, which can overcome the problem that the graphene material itself is not easy to disperse and reduce agglomeration. The coating composition of the present application can provide a coating with uniform appearance and improved antistatic properties while maintaining its own advantages.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of antistatic coatings, especially the field of antistatic coatings in electrical equipment. More specifically, the present invention relates to a graphene premix, and a coating composition and a coated product containing the graphene premix. Background Art

[0002] With the rapid development of the economy, coatings are required to have excellent antistatic properties in many coating applications. As an example, metal pipes or containers used for chemical production and transportation (such as oil pipelines, oil storage tanks and tank cars) are prone to corrosion and static electricity problems. In particular, in applications that are prone to static electricity (for example, friction in a relatively dry environment, or close to electronic or electrical equipment, such as in a machine room, etc.), static electricity accumulation can easily cause equipment paralysis or even serious safety hazards.

[0003] In the current field of antistatic coatings, in order to improve the antistatic performance of the coating, it is usually necessary to add a large amount (usually more than 3% by weight) of conductive additives to the coating. However, many conductive additives have the problem of insufficient compatibility with other components in the coating, which easily causes the cured coating to blister and powder. In addition, some conductive additives (such as carbon nanotubes) have the disadvantages of high cost and complex production process, which greatly limits their application range. Summary of the invention

[0004] In view of this, the inventors found that there is a need for a conductive premix that is relatively low in cost, easy to disperse and has excellent antistatic properties.

[0005] The above needs can be met by employing the graphene premixes, coating compositions, and coated articles described herein.

[0006] A first aspect of the present application provides a graphene premix, comprising: at least one dispersant having a sulfonimide moiety, at least one glycidyl ether compound, and at least one graphene.

[0007] A second aspect of the present application provides a coating composition comprising a film-forming resin and the graphene premix according to the first aspect.

[0008] A third aspect of the present application provides a coated product comprising: a substrate having at least one surface; and a coating composition described herein or a cured coating thereof directly or indirectly coated on at least a portion of the at least one surface of the substrate.

[0009] The inventors were surprised to find that the graphene premix described in the present application is a conductive premix that is very easy to disperse and has excellent antistatic properties. Moreover. The graphene premix described in the present application can be quickly and evenly mixed with other components of the coating composition without the need for dispersing means such as ultrasound or grinding. The graphene premix and coating composition of the present application have excellent antistatic properties, and have the advantages of low cost and easy dispersion, which can overcome the problem that the graphene material itself is not easy to disperse and reduce agglomeration. The coating composition of the present application can provide a coating with uniform appearance and improved antistatic properties while maintaining its own advantages.

[0010] Moreover, the inventors have also found that the dispersibility and antistatic properties of the graphene premix can be further improved by selecting appropriate components (eg, graphene materials, dispersants) or adjusting the parameters of the components.

[0011] The above summary of the present application is not intended to describe each disclosed embodiment or every implementation of the present application. Illustrative embodiments are more particularly exemplified in the following description. DETAILED DESCRIPTION

[0012] definition

[0013] As used herein, "a", "an", "the", "at least one" and "one or more" and the absence of quantifiers may be used interchangeably unless otherwise indicated. Thus, for example, a coating composition comprising "an" additive may be interpreted to mean that the coating composition comprises "one or more" additives. Unless otherwise indicated herein, the use of the singular form herein is intended to include the plural form.

[0014] Unless otherwise expressly stated, the use of the terms "includes," "comprising," "containing," and "having" should generally be interpreted as open-ended and non-restrictive. For example, where a composition is described as including or comprising specific components, it is expected that optional components not mentioned in the present application are not excluded from the composition, and it is expected that the composition can be composed of or consist of the mentioned components, or where a method is described as including or comprising specific process steps, it is expected that optional process steps not mentioned in the present application are not excluded from the method, and it is expected that the method can be composed of or consist of the mentioned process steps.

[0015] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.

[0016] Unless otherwise indicated, each point or single value between the endpoints of a range is included in the range. For example, a range of 1 to 5 includes the values ​​1, 1.5, 2, 2.75, 3, 3.80, 4, 5, etc. Moreover, a disclosed numerical range includes all subset ranges within the broader range, for example, a range of 1 to 5 includes subranges 1 to 4, 1.5 to 4.5, 1 to 2, etc. Thus, each point or single value can be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits, and the resulting range belongs to the content explicitly disclosed in this application.

[0017] As used herein, the term "or" is inclusive. That is, the phrase "A or (or) B" means "A, B, or both A and B", which may also be abbreviated as "A and / or B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist). In contrast, the exclusive "or (or)" is represented herein, for example, by terms such as "either A or B" and "one of A or B".

[0018] When used in the context of a "coating applied to a surface or substrate," the term "on" includes coatings applied directly or indirectly to a surface or substrate. Thus, for example, a coating applied to a primer layer on a substrate is counted as a coating applied to the substrate.

[0019] The terms "preferred" and "preferably" refer to embodiments of the present application that may provide certain benefits in certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. In addition, the description of one or more preferred embodiments does not mean that other embodiments are not applicable, and is not intended to exclude other embodiments from the scope of the present application.

[0020] Graphene premix

[0021] The graphene premix according to the first aspect of the present application comprises: at least one dispersant having a sulfonimide moiety, at least one glycidyl ether compound, and at least one graphene. In some embodiments, the graphene premix is ​​composed of the following substances: at least one dispersant having a sulfonimide moiety, at least one glycidyl ether compound, and at least one graphene

[0022] During the research process, the inventors found that graphene has the advantages of light weight, stable chemical properties, good wear resistance, excellent electrical conductivity, thermal conductivity, and extremely high carrier mobility, and is a very promising antistatic agent; however, graphene has many problems in coatings (especially when used as a powder). For example, the high specific surface area and van der Waals force of graphene easily cause the powder to foam in the liquid, which is very easy to float and disperse, and it is difficult to add materials. Moreover, when construction workers directly add graphene powder to the liquid, graphene is very easy to agglomerate and restack, and it is difficult to form a well-dispersed composition. Therefore, how to obtain a graphene premix with good dispersibility is a problem that needs to be solved urgently.

[0023] The inventors found during the research that graphene can form a relatively stable graphene premix with glycidyl ether compounds. Without being limited by theory, it is believed that glycidyl ether compounds have epoxy groups and extremely low surface tension, and can be used as epoxy diluents to significantly reduce the viscosity of the system without affecting the performance of the cured coating.

[0024] In some embodiments, preferably, the glycidyl ether compound is selected from one or more of 2-ethylhexyl glycidyl ether, C10-C18 alkyl glycidyl ether, neopentyl glycol diglycidyl ether, butanediol diglycidyl ether, and butyl glycidyl ether. More preferably, the glycidyl ether compound is C10-C18 alkyl glycidyl ether, and particularly preferably C12-14 alkyl glycidyl ether (AGE).

[0025] In some embodiments, the amount of the glycidyl ether compound may be 75 wt % or more, preferably 80 wt % or more, more preferably 85 wt % or more, and particularly preferably 90 wt % or more, based on the total weight of the graphene premix. The amount of the glycidyl ether compound may be 99 wt % or less, preferably 98 wt % or less, and more preferably 96 wt % or less, based on the total weight of the graphene premix. For example, the amount of the glycidyl ether compound may be about 82 wt %, 85 wt %, 87 wt %, 88 wt %, 89 wt %, 90 wt %, 91 wt %, 92 wt %, 93 wt %, 94 wt %, 95 wt %, or may be in a range consisting of any of these values, based on the total weight of the graphene premix.

[0026] The inventors have found that the combination of graphene and glycidyl ether compounds can improve the dispersibility of graphene premixes without the need to use or using other organic solvents (such as ethanol, n-butanol, xylene, toluene, benzyl alcohol, N-methylpyrrolidone, etc.) in very small amounts. Preferably, the amount of organic solvent is no more than 3 weight %, more preferably no more than 2 weight %, even more preferably no more than 1 weight %, and further preferably no more than 0.3 weight % of the total weight of the graphene premix. For example, the graphene premix contains no more than 0.5 weight %, no more than 0.1 weight %, and no more than 0.05 weight % of organic solvent. In some embodiments, the graphene premix contains an organic solvent, or does not contain a specially added organic solvent. Preferably, the graphene premix does not contain an alcohol or ketone organic solvent. More preferably, the graphene premix does not contain an organic solvent, such as ethanol, n-butanol, xylene, toluene, benzyl alcohol, N-methylpyrrolidone, etc. This helps to reduce the VOC of the graphene premix, the coating composition containing it, and the cured coating.

[0027] In some embodiments, the dispersant may be or include an ionic liquid dispersant, a polymeric dispersant, or a combination thereof. The dispersant may be or include a polymer having a sulfonimide group, such as a high molecular weight block copolymer. In some exemplary embodiments, the dispersant may be or include one or more of a polytrifluoromethylsulfonimide block copolymer, a copolymer of polystyrenesulfonimide and ethyl acrylate.

[0028] Preferably, the dispersant is an ionic liquid type dispersant. In this context, an ionic liquid is a compound comprising a cation and an anion, wherein at least one ion (especially at least the cation) is organic. In some embodiments, both the cation and the anion in the ionic liquid are organic.

[0029] The inventors found that, unlike non-ionic dispersants, the use of ionic liquid dispersants can not only improve the dispersion effect of graphene, but also further enhance the antistatic performance. This is very unexpected. Without being limited by theory, it is believed that graphene is a carbon sp 2 Hybridized orbitals form two-dimensional nanomaterials. The agglomeration problem of graphene is mainly affected by the delocalized π electrons in the graphene structure. The cations in the ionic liquid dispersant can produce cation-π non-covalent interactions with the delocalized π electrons in the graphene, resulting in the enrichment of cation-containing ionic liquids on the graphene surface, thereby effectively hindering the agglomeration caused by the π-π interaction formed between graphene layers; moreover, through the modification of the graphene surface by ionic liquids, the ions and electrons in the graphene structure can be redistributed, which will also affect the performance of graphene-based coatings and promote the rapid dispersion of graphene in liquids.

[0030] The ionic liquid dispersant may be or include one or more of imidazole ionic liquids, pyridine ionic liquids, quaternary ammonium salt ionic liquids, quaternary phosphonium salt ionic liquids and piperidine ionic liquids. Preferably, the ionic liquid dispersant may be or include one or more of imidazole ionic liquids and quaternary ammonium salt ionic liquids.

[0031] Ionic liquid dispersants can include alkyl quaternary ammonium cations or imidazolium cations. The alkyl quaternary ammonium cations can have 4 to 25 carbon atoms, preferably 4 to 20 carbon atoms. For example, the alkyl quaternary ammonium cations can have 5, 6, 7, 8, 9, 10, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23 or 24 carbon atoms. The imidazolium cations can have 5 to 25 carbon atoms, preferably 5 to 20 carbon atoms. For example, the imidazolium cations can have 5, 6, 7, 8, 9, 10, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23 or 24 carbon atoms.

[0032] Examples of cations in the ionic liquid type dispersant may include, but are not limited to, tetramethylammonium, tetraethylammonium, tetrabutylammonium, tetrahexylammonium, tetraoctylammonium, trimethylethylammonium, trimethylpropylammonium, trimethylbutylammonium, trimethylpentylammonium, trimethylhexylammonium, trihexylmethylammonium, triethylpropylammonium, triethylbutylammonium, triethylpentylammonium, tributylmethylammonium, tributylethylammonium, tributylpropylammonium, tripropylmethylammonium, tripropylethylammonium, tripropylbutylammonium, tripentylammonium, tripentylammonium, tripentylammonium, tripentylammonium, triheptylmethylammonium, triheptylethylammonium, triheptylpropylammonium, trioctylmethylammonium, trioctyl Ethyl ammonium, trioctylpropyl ammonium, tri-(2-hydroxyethyl)methyl ammonium, tri-(2-hydroxyethyl)ethyl ammonium, di-(2-hydroxyethyl)dimethyl ammonium, 1,3-dimethylimidazolium, 1-ethyl-3-methylimidazolium, 1-propyl-3-methylimidazolium, 1-butyl-3-methylimidazolium, 1-pentyl-3-methylimidazolium, 1-hexyl-3-methylimidazolium, 1,2,3-trimethylimidazolium, 1,3-diethylimidazolium, 1,3-dibutylimidazolium, 1-ethyl-2,3-dimethylimidazolium, 1-butyl-2,3-dimethylimidazolium, 1-(2-hydroxyethyl)-3-methylimidazolium imidazolium, 1-(3-hydroxypropyl)-3-methylimidazolium, 1-(2-hydroxypropyl)-3-methylimidazolium, 1-(4-hydroxy-butyl)-3-methylimidazolium, 1-(3-hydroxy-butyl)-3-methylimidazolium, 1-(2-hydroxy-butyl)-3-methylimidazolium, 1-(2-methoxyethyl)-3-methylimidazolium, 1-(3-methoxypropyl)-3-methylimidazolium, 1-(2-methoxypropyl)-3-methylimidazolium, 1-(4-methoxy-butyl)-3-methylimidazolium, 1-(3-methoxy-butyl)-3-methylimidazolium, 1-(2-methoxyethyl)-3-methylimidazolium, -butyl)-3-methylimidazolium, 1-(2-ethoxyethyl)-3-methylimidazolium, 1-(3-ethoxypropyl)-3-methylimidazolium, 1-(2-ethoxypropyl)-3-methylimidazolium, 1-(4-ethoxy-butyl)-3-methylimidazolium, 1-(3-ethoxy-butyl)-3-methylimidazolium, 1-(2-ethoxy-butyl)-3-methylimidazolium, 1-allyl-3-methylimidazolium and 1-allyl-2,3-dimethylimidazolium, 1-vinyl-3-methylimidazolium, 1-vinyl-3-ethylimidazolium and 1-vinyl-3-butylimidazolium.

[0033] It is particularly preferred that the cation in the ionic liquid dispersant may be one or more of a tributylmethylammonium cation, a tripropylmethylammonium cation, a triethylmethylammonium cation, an ethylbutylmethylammonium cation, a propylbutylmethylammonium cation, a trimethylethylammonium cation, a trimethylpropylammonium cation, a trimethylbutylammonium cation, a trimethylpentylammonium cation, a trimethylhexylammonium cation, 1-ethyl-3-methylimidazolium, 1,3-diethylimidazolium, 1-ethyl-3-propylimidazolium and 1-propyl-3-methylimidazolium.

[0034] Advantageously, a cation with a large steric hindrance is used, such as a quaternary ammonium cation with a relatively long carbon chain or an imidazolium with a heterocycle. Further preferred cations may be tributylmethylammonium cations and 1-ethyl-3-methylimidazolium, in particular tributylmethylammonium cations. For example, in some particularly preferred embodiments, the cation in the ionic liquid dispersant may be a tri-n-butylmethylammonium cation.

[0035] In some embodiments, the ionic liquid dispersant has a fluorinated functional group, preferably a fluorinated sulfonyl imide anion or moiety. Examples of sulfonyl imide anions include, but are not limited to, perfluoroalkylsulfonyl imides, such as bis(fluorosulfonyl)imide ([N(SO2F)2] – ), bis(trifluoromethanesulfonyl)imide ([N(SO2CF3)2] – ), bis(pentafluoroethanesulfonyl)imide ([N(SO2CF2CF3)2] – ), bis(heptafluoropropanesulfonyl)imide (e.g. [N(SO2CF2CF2CF3)2] – ), bis(nonafluorobutanesulfonyl)imide (e.g. [N(SO2(CF2)3CF3)2] – ), (fluorosulfonyl)(trifluoromethanesulfonyl)imide ([N(SO2F)(SO2CF3) – ]), (fluorosulfonyl)(pentafluoroethanesulfonyl)imide ([N(SO2F)(SO2CF2CF3) – ]), (fluorosulfonyl)(heptafluoropropanesulfonyl)imide (e.g. [N(SO2F)(SO2(CF2)2CF3) – ]), (fluorosulfonyl)(nonafluorobutanesulfonyl)imide (e.g. [N(SO2F)(SO2(CF2)3CF3) – ]), (trifluoromethanesulfonyl)(pentafluoroethanesulfonyl)imide (e.g. [N(SO2CF3)(SO2CF2CF3)] – ), (trifluoromethanesulfonyl)(heptafluoropropanesulfonyl)imide (e.g. [N(SO2CF3)(SO2(CF2)2CF3) –]), (trifluoromethanesulfonyl)(nonafluorobutanesulfonyl)imide (e.g. [N(SO2CF3)(SO2(CF2)3CF3) – ]), (pentafluoroethanesulfonyl)(heptafluoropropanesulfonyl)imide (e.g. [N(SO2CF2CF3)(SO2(CF2)2CF3) – ]), (pentafluoroethanesulfonyl)(nonafluorobutanesulfonyl)imide (e.g. [N(SO2CF2CF3)(SO2(CF2)3CF3) – ]) and (heptafluoropropanesulfonyl)(nonafluorobutanesulfonyl)imide (e.g. [N(SO2(CF2)2CF3)(SO2(CF2)3CF3) – ]).

[0036] Preferably, the ionic liquid dispersant is or comprises one or more of tri-n-butylmethylammonium bis(trifluoromethylsulfonyl)imide, tri-isobutylmethylammonium bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-methylimidazole bis(trifluoromethylsulfonyl)imide, 1,3-diethylimidazole bis(trifluoromethylsulfonyl)imide, and trimethylpropylammonium bis(trifluoromethylsulfonyl)imide. More preferably, the ionic liquid dispersant is or comprises one or more of tri-n-butylmethylammonium bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-methylimidazole bis(trifluoromethylsulfonyl)imide, and 1-ethyl-3-ethylimidazole bis(trifluoromethylsulfonyl)imide. Particularly preferably, the ionic liquid dispersant is or comprises tri-n-butylmethylammonium bis(trifluoromethylsulfonyl)imide.

[0037] The inventors have found that the use of the ionic liquid dispersant described above, especially the ionic liquid dispersant formed by the combination of the preferred cations and the preferred anions described above, can not only greatly improve the dispersion effect of graphene, but also greatly improve the antistatic performance (for example, the surface resistance of the cured coating reaches 10 8 Ω, 10 7 Ω, even 10 6 Ω). This is very unexpected. The inventors found that, without using a conductive agent (such as graphene, carbon nanotubes), a relatively large amount of ionic liquid dispersant (such as 5 wt % or more) is required to make the coating composition and the cured coating show slightly improved antistatic properties, but the improvement in antistatic properties is still very limited. For example, the surface resistance of the coating reaches 10 10 Without being limited by theory, when an ionic liquid dispersant formed by a combination of the preferred cations and the preferred anions described above is used, the cations and anions can interact with the sheet structure of graphene, further inhibiting the formation of π-π interactions between graphene layers and reducing agglomeration, thereby further improving dispersibility and antistatic properties at the same time.

[0038] In some embodiments, the molecular weight of the ionic liquid dispersant is 200-1000 g / mol, preferably 300-800 g / mol, more preferably 350-600 g / mol. For example, the molecular weight of the ionic liquid dispersant can be 200 g / mol, 250 g / mol, 300 g / mol, 350 g / mol, 400 g / mol, 450 g / mol, 500 g / mol, 550 g / mol, 600 g / mol, 650 g / mol, 700 g / mol, 750 g / mol, 800 g / mol, 850 g / mol, 900 g / mol, 950 g / mol, 1000 g / mol, or can be in the range consisting of any of these values.

[0039] In some embodiments, the graphene premix comprises or consists of the following, based on the total weight of the graphene premix:

[0040] 0.5 to 20 wt% of a dispersant having a sulfonimide moiety,

[0041] 75 to 98% by weight of a glycidyl ether compound, and

[0042] 1 wt % to 10 wt % graphene.

[0043] In some embodiments, the amount of the dispersant can be 0.5 wt % to 20 wt %, preferably 1 wt % to 15 wt %, based on the total weight of the graphene premix. For example, the amount of the dispersant can be 0.8 wt %, 1 wt %, 1.5 wt %, 2.0 wt %, 2.5 wt %, 3.0 wt %, 3.5 wt %, 4.0 wt %, 4.5 wt %, 5.0 wt %, 5.5 wt %, 6.0 wt %, 6.5 wt %, 7.0 wt %, 7.5 wt %, 8 wt %, 10 wt %, 12 wt %, 15 wt %, 18 wt % or 20 wt %, or can be in a range consisting of any of these values.

[0044] In some embodiments, graphene can be one or more of graphene, graphene oxide, functionalized graphene in an eigenstate. Functionalized graphene has one or more of hydroxyl, carboxyl, carbonyl, amino, sulfhydryl. The average particle size D50 of graphene powder is 1-20 microns. In some embodiments, the average particle size D50 of graphene powder is 1-10 microns, preferably 1-5 microns. For example, the average particle size D50 of graphene powder can be 1 micron, 2 microns, 3 microns, 4 microns, 5 microns, 8 microns, 10 microns, 12 microns, 15 microns, 18 microns or 20 microns.

[0045] Graphene can be prepared by methods known in the art. For example, the preparation method of graphene can be micromechanical exfoliation, chemical vapor deposition, liquid phase exfoliation, chemical redox method and electrochemical oxidation method, etc. Preferably, graphene is prepared by redox method.

[0046] The inventors have found that by controlling the number of layers of graphene, the antistatic property of the graphene premix can be changed, and the antistatic property of the coating composition and the cured coating can be changed. Preferably, the graphene is 1-2 layers, 2-3 layers or 3-4 layers of graphene. Particularly preferably, the graphene is 3-4 layers of graphene. The number of layers of graphene can be measured by methods known in the art, such as statistical analysis using a scanning electron microscope (SEM).

[0047] It should be noted that although the number of graphene layers is expressed in a manner that appears to be a numerical range, such as 3-4, the number of layers actually represents the average number of graphene layers and the main distribution of the number of layers. In other words, graphene with 4-6 layers and graphene with 3-4 layers are actually two completely different materials, and the disclosure of graphene with 4-6 layers cannot be considered to disclose or teach graphene with 3-4 layers.

[0048] Coating composition

[0049] A second aspect of the present application provides a coating composition comprising a film-forming resin and the graphene premix according to the first aspect.

[0050] In some embodiments, the weight ratio of graphene to film-forming resin in the graphene premix is ​​0.1:100 to 0.8:100. More preferably, the weight ratio of graphene to film-forming resin in the graphene premix is ​​0.1:100 to 0.5:100. For example, the weight ratio of graphene to film-forming resin in the graphene premix is ​​0.1:100, 0.2:100, 0.3:100, 0.4:100, 0.5:100, 0.6:100, 0.7:100 or 0.8:100, or can be in a range consisting of any of these values.

[0051] In some embodiments, the weight ratio of the dispersant to the film-forming resin in the graphene premix is ​​0.2:100 to 5:100. More preferably, the weight ratio of the dispersant to the film-forming resin in the graphene premix is ​​0.25:100 to 4:100. For example, the weight ratio of the dispersant to the film-forming resin in the graphene premix is ​​0.2:100, 0.25:100, 0.3:100, 0.4:100, 0.5:100, 0.6:100, 0.7:100, 0.8:100, 0.9:100, 1:100, 1.2:100, 1.5:100, 2:100, 2.5:100, 3:100, 3.5:100, 4:100, 4.5:100 or 5:100, or can be in a range consisting of any of these values.

[0052] In some embodiments, the film-forming resin is one or more of bisphenol A epoxy resin, alicyclic epoxy resin, bisphenol F epoxy resin, novolac epoxy resin, acrylic resin, alkyd resin, polyurethane, and acrylic resin. Preferably, the film-forming resin is one or more of bisphenol A epoxy resin, alicyclic epoxy resin, bisphenol F epoxy resin, novolac epoxy resin

[0053] In some embodiments, the epoxy resin may include a novolac epoxy resin, a bisphenol A epoxy resin, or a combination thereof. In some embodiments, the novolac epoxy resin may have an epoxy equivalent weight of less than 300, preferably less than 250, more preferably less than 200 g / eq. For example, the novolac epoxy resin may have an epoxy equivalent weight of about 160, about 165, about 170, about 185, about 190, about 195 g / eq. In some embodiments, the bisphenol A epoxy resin may have an epoxy equivalent weight of less than 300, preferably less than 250, more preferably less than 200 g / eq. For example, the bisphenol A epoxy resin may have an epoxy equivalent weight of about 180, about 185, about 190, about 195 g / eq.

[0054] In some embodiments, the epoxy resin may include novolac epoxy resin and bisphenol A epoxy resin. Preferably, the weight ratio of bisphenol A epoxy resin to novolac epoxy resin is 1:1 to 10:1, preferably 1.5:1 to 8:1, preferably 2:1 to 5:1, such as 3:1, 4:1, 6:1, 7:1.

[0055] Based on the total weight of the A component, the amount of the epoxy resin may be 20-48 wt %, preferably 25-45 wt %, more preferably 30-40 wt %, such as about 35 wt %, about 28 wt %.

[0056] In some embodiments, the coating composition is a two-component coating composition, and the two-component coating composition further comprises a curing agent component. Preferably, the curing agent component comprises at least one alicyclic amine curing agent.

[0057] For example, the two-component coating composition comprises an A component and a B component, wherein the A component comprises at least one epoxy resin and the B component comprises at least one alicyclic amine curing agent.

[0058] In the two-component coating composition described herein, component B includes an alicyclic amine curing agent. The inventors have found that compared with other curing agents (e.g., polyamide curing agents, cardanol curing agents, aliphatic polyamine curing agents, aromatic amine curing agents), the alicyclic amine curing agent has a cyclic structure, excellent heat resistance, and after reacting with epoxy resin, forms a dense network structure coating, which blocks hot water penetration and corrosion with metal. By selecting a suitable alicyclic amine curing agent, the hot water resistance of the coating can be further improved.

[0059] In some embodiments, the alicyclic amine curing agent may have an active hydrogen equivalent of 80-140 g / eq, preferably 90-110 g / eq, such as about 95 g / eq, about 100 g / eq, about 105 g / eq, about 110 g / eq, about 115 g / eq.

[0060] In the two-component coating composition described herein, the relative amounts of component A and component B can be adjusted as needed. In some embodiments, the volume ratio of component A to component B is 1:1 to 10:1, preferably 1:1 to 10:1, more preferably 2:1 to 8:1, such as 3:1, 4:1, 5:1, 6:1, 7:1.

[0061] The coating composition according to the present application may also include conventional additives, which do not adversely affect the coating composition or the cured coating obtained therefrom. Suitable additives include, for example, those reagents that improve the processing properties or manufacturing properties of the composition, enhance the aesthetics of the composition, improve the coating composition or the specific functional properties or characteristics (such as adhesion to the substrate) of the cured composition obtained therefrom, or reduce costs. The additives that may be included are, for example, pigments, lubricants, film-forming aids, wetting agents, plasticizers, defoamers, colorants, antioxidants, flow control agents, thixotropic agents, matte powders, dispersants, adhesion promoters, thickeners, pH regulators, curing catalysts, or combinations thereof. The content of each optional component is sufficient to achieve its intended purpose, but preferably, such content does not adversely affect the coating composition or the cured coating obtained therefrom. In some preferred embodiments, the coating composition may include defoamers, film-forming aids, wetting agents, leveling agents, thickeners, matte powders, or any combination thereof as conventional additives. According to the present application, the total amount of conventional additives is 0.1% by weight to 25% by weight, for example, about 10% by weight, relative to the gross weight of the coating composition. In some embodiments, the amount of dispersant may be 0.1-1 wt %, the amount of defoamer may be 0.1-0.3 wt %, the amount of wetting agent may be 0.5-2 wt %, the amount of leveling agent may be 0.5-2 wt %, or the amount of thixotropic agent may be 0.1-1 wt %.

[0062] In the coating composition in the present application, relatively low amount of graphene premix can be used, still can realize good antistatic performance and dispersibility. This is completely different from the common cognition in the art. Before the present application, those skilled in the art usually need to add a large amount of (usually 5 weight %, 15 weight % or more) of conductive filler, such as conductive mica powder, conductive barium sulfate, ionic liquid conductive agent, in order to obtain antistatic coating. However, the inventors have found that adding such a large amount of conductive filler (especially conductive mica powder) can cause the viscosity of coating to rise, have a strong impact on the sprayability, dispersibility and wettability of substrate of coating, so that construction performance is significantly reduced. Adding fillers with high conductivity such as carbon nanotubes can significantly increase the cost of coating, thereby limiting the scope of application of coating.

[0063] According to the present application, the two-component coating composition can be prepared as follows: before application, component A and component B are simply mixed in a mixing device in a predetermined ratio. The mixed coating composition can be applied using various methods familiar to those skilled in the art, including spraying (e.g., air-assisted, airless or electrostatic spraying), brushing, roller coating, overflow coating and dipping. In one embodiment of the present application, the mixed coating composition is applied by spraying. The coating composition can be applied to various wet film thicknesses. In an embodiment of the present application, the wet film thickness preferably provides a dry film thickness of about 13 to about 260 μm, and more preferably about 75 to about 150 μm. It can be cured by air drying the applied coating or by accelerating curing using various drying devices familiar to those skilled in the art (e.g., oven).

[0064] Coated products

[0065] A third aspect of the present application provides a coated product comprising: a substrate having at least one surface; and a coating composition described herein or a cured coating thereof directly or indirectly coated on at least a portion of the at least one surface of the substrate.

[0066] In some embodiments, the substrate is selected from metal, wood, wood composite, paper, plastic, fabric, ceramic, cement material or any combination thereof. The substrate can be wooden furniture, barbecue stove, boiler, furnace, heater, high-power lighting, heating pipe, automobile body primer, automobile or motorcycle exhaust system, engine hood, muffler, engine parts, fireplace, chimney, grid, oven, steam pipeline, heat exchanger and any surface usually exposed to high heat for a long time. In some embodiments, the substrate can be metal or polymer composite material. As the metal for making the coated product, it can be any suitable metallic substrate known in the art. As an exemplary illustration, the substrate can be an iron substrate, an aluminum substrate, carbon steel, stainless steel, high-strength steel, aluminum alloy. The substrate can also be glass fiber or carbon fiber reinforced plastic. In some embodiments, the substrate can be a sheet molding material (SMC, Sheet Molding Compound). For example, the substrate can be a glass fiber / PA6 composite material.

[0067] The coating composition of the present application can be directly coated on the substrate, and can also be coated on the coating on the substrate. In some embodiments, the coating composition of the present application can be used in conjunction with a primer. In this case, the goods of the present application include a substrate, a primer layer and a coating formed by the coating composition of the present application. In other embodiments of the present application, the coating composition of the present application can be applied without a primer, and is directly coated on the principal surface of the substrate.

[0068] As the metal substrate for manufacturing the product of the present application, any suitable metal substrate known in the art can be used. As an example, the metal substrate can include an iron substrate, an aluminum substrate, carbon steel or stainless steel.

[0069] According to the present application, the coated article can be prepared, for example, by the following steps: (1) providing a polished metal substrate; (2) using a coating process to sequentially coat and form one or more layers of the coating composition described herein on the metal substrate, and obtaining a cured coating after curing.

[0070] The metal products of the present application can be used for the following end applications, including but not limited to: refrigerated containers and non-refrigerated transport containers (such as dry cargo containers) from suppliers or manufacturers including China International Marine Containers (CIMC), Graaff Transportsysteme Gmbh, Maersk Line, and other suppliers or manufacturers known to those skilled in the art; chassis, trailers (including semi-trailers), rail vehicles, truck bodies, ships, bridges, petrochemical storage tank linings, building skeletons, and prefabricated or ready-made metal parts that require temporary indoor or outdoor corrosion protection during manufacturing. Additional uses include metal corners, channels, beams (such as I-beams), pipes, tubes, plates or other components that can be welded into these or other metal parts.

[0071] The graphene premix and coating composition described herein can provide a coating having a uniform and smooth appearance. The appearance of the coating can be confirmed by visual observation. In some embodiments, no aggregated particles are observed in the cured coating, and the coating film is uniform.

[0072] The graphene premix and coating compositions described herein can provide coatings with excellent electrical conductivity. In particular, the cured coatings described herein meet the industry's requirements for electrostatic conductivity of coatings on metallic substrates. In some embodiments, the surface resistivity of the cured coating is 1×10 6 Up to 1×10 10 Ω, preferably 1×10 6 Up to 1×10 9 Ω, for example 1×10 9 Ω、1×10 8 Ω、1×10 9 Ω. The surface resistivity described herein can be measured according to a common standard, for example, according to GB / T 1410-2006. Unless otherwise specified, the surface resistivity is measured at 23±2° C. and 50±5% relative humidity.

[0073] Example

[0074] The following examples more specifically describe the disclosure of the present application, and these examples are only used for illustrative explanations, because it is obvious to those skilled in the art to make various modifications and variations within the scope of the present disclosure. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on weight. Moreover, all reagents used in the examples are commercially available and can be used directly without further processing.

[0075] Test Method

[0076] Surface resistivity: According to GB / T 1410-2006, the resistivity of the sample surface is measured at 23±2℃ and 50±5% relative humidity. The unit is Ω.

[0077] Dispersion performance: Without using any dispersing means such as ultrasound or grinding, simply mix the components and then visually observe and evaluate whether there are any changes in the coating after 1 month of hot storage at 50°C and / or whether the coating film shows agglomeration after curing at 50°C for 5 hours.

[0078] 0- means that there is no stratification or gelation of the coating after hot storage, no aggregated particles are observed in the cured coating film, and the coating film is uniform.

[0079] 1-Indicates that there is no stratification or gelation of the coating after hot storage, and aggregated particles are observed in the cured coating film, which are small and evenly distributed.

[0080] 2-Indicates that the coating is stratified or gelled after hot storage, or obvious aggregated particles are observed in the cured coating film, and the particles are coarse and unevenly distributed.

[0081] 3-Indicates that the coating is stratified or gelled after hot storage, and obvious aggregated particles are observed in the cured coating film. The particles are coarse and unevenly distributed.

[0082] Material

[0083] Graphene sample 1: contains 90 wt% of C12-14 alkyl glycidyl ether (AGE), 5 wt% of dispersant A and 5 wt% of graphene powder, wherein the number of layers of the graphene powder is 3-4 and the average particle size is 2-3 microns. The sample has a wet powder appearance.

[0084] Graphene sample 2: contains about 97 wt% N-methylpyrrolidone (NMP) and 3 wt% graphene, wherein the number of layers of graphene powder is 3-4 and the average particle size is 2-3 microns. The sample has a mud-like appearance.

[0085] Graphene sample 3: contains about 85 wt% benzyl alcohol (BnOH) and 3 wt% graphene, wherein the number of layers of graphene powder is 4-6 and the average particle size is 2-3 micrometers. The sample has a slurry appearance.

[0086] Carbon nanotube sample: Concentrate TUBALL MATRIX 208 from OCSiAl, containing 10% by weight of carbon nanotubes. The sample had a sludge-like appearance.

[0087] Ionic liquid type dispersant: tri-n-butylmethylammonium bis(trifluoromethylsulfonyl)imide (hereinafter, represented by dispersant A), trimethylpropylammonium bis(trifluoromethylsulfonyl)imide (hereinafter, represented by dispersant B), 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide salt (hereinafter, represented by dispersant C), 1-ethyl-3-methylimidazolium ethyl sulfate salt (hereinafter, represented by dispersant D), butanol solution of tetraalkylammonium sulfate ether (80% by mass) (hereinafter, represented by dispersant E). It can be seen that both 1-ethyl-3-methylimidazolium ethyl sulfate salt (dispersant D) and butanol solution of tetraalkylammonium sulfate ether (dispersant E) do not contain a sulfonyl imide portion.

[0088] Polymeric dispersants: BYK-163, a high molecular weight modified polyurethane block copolymer solution containing pigment-affinity groups (hereinafter referred to as dispersant F); XL-30, an imidized isobutylene / dimethylaminopropylmaleimide / ethoxymaleimide / maleic anhydride copolymer (hereinafter referred to as dispersant G).

[0089] Glycidyl ether compounds: C12-14 alkyl glycidyl ether (AGE), CAS number: 68609-97-2.

[0090] Resin component: comprising 12 parts of novolac epoxy resin, 36 parts of bisphenol A epoxy resin, 5 parts of additives, 35 parts of fillers and 12 parts of solvents. The epoxy equivalent of the novolac epoxy resin is 180 g / eq, and the epoxy equivalent of the bisphenol A epoxy resin is 190 g / eq.

[0091] Curing agent component: alicyclic amine curing agent is used, and the amine value is about 251 mg KOH / g.

[0092] Example 1

[0093] The effect of the number of layers and composition of the graphene samples (premix) as well as the carbon nanotube samples and pure dispersant A on the antistatic properties of the coatings was tested.

[0094] Each sample is added to a coating composition containing epoxy resin. The addition amount in Table 1 is the weight of the effective ingredient (such as graphene, carbon nanotube or ionic liquid type dispersant) in the sample that plays an antistatic role based on the epoxy resin in the coating composition. The resin component and the curing agent component are mixed in a volume ratio of 4:1, and then applied to a steel plate and cured. The performance of the cured coating is tested.

[0095] Table 1:

[0096] sample Addition amount Surface resistivity, Ω Carbon nanotube samples 0.02 wt% <![CDATA[10 8 ]]> Dispersant A >1 wt% <![CDATA[10 10 ]]> Graphene sample 1 0.3 wt% <![CDATA[10 8 ]]> Graphene sample 2 0.3 wt% <![CDATA[10 8 ]]> Graphene sample 3 >1 wt% <![CDATA[10 11 ]]>

[0097] From the results in Table 1, it can be seen that, compared with graphene with 4 to 6 layers, the use of a smaller amount of graphene with 3 to 4 layers can significantly improve the electrostatic conductivity of the coating, and can even achieve an antistatic effect comparable to that of carbon nanotube samples. In particular, the price per unit weight of carbon nanotubes is significantly higher than the price per unit weight of graphene, which makes the low-priced graphene more attractive for large-scale commercial applications.

[0098] Furthermore, it can be seen that when using graphene having 3 to 4 layers, an organic solvent (eg, alcohol and ketone organic solvents) is not necessary.

[0099] Example 2

[0100] The effects of dispersants on antistatic and graphene dispersion properties were tested.

[0101] The resin component and the curing agent component were mixed in a volume ratio of 4:1, and then coated on a steel plate and cured. The cured coating was used as a blank control sample.

[0102] The blank control experiment was repeated, but the difference was that 0.2 wt % of graphene sample 1 (containing dispersant A) was added to the resin component relative to the weight of the epoxy resin. In other experiments, dispersant A was replaced by dispersant B, dispersant C, dispersant D, dispersant E, dispersant F and dispersant G, respectively.

[0103] The properties of each cured coating were tested. The results are shown in Table 2.

[0104] Table 2:

[0105] Dispersibility Surface resistivity, Ω blank 2 <![CDATA[10 9 ]]> Dispersant A 0 <![CDATA[10 7 -10 8 ]]> Dispersant B 1 <![CDATA[10 8 ]]> Dispersant C 1 <![CDATA[10 8 ]]> Dispersant D 2 <![CDATA[10 9 ]]> Dispersant E 2 <![CDATA[10 9 ]]> Dispersant F 2 <![CDATA[10 9 ]]> Dispersant G 3 <![CDATA[10 9 ]]>

[0106] As can be seen from Table 2, the graphene premix, coating composition and coated article of the present application can simultaneously obtain improved dispersibility and antistatic properties. In particular, when an ionic liquid dispersant containing a sulfonimide moiety is combined with graphene having 3-4 layers, both the dispersibility and antistatic properties are further improved.

[0107] Although the present application is described with reference to a large number of embodiments and examples, it will be appreciated by those skilled in the art that other embodiments may be designed based on the content disclosed in the present application. It will be readily apparent to those skilled in the art that changes may be made to the present application without departing from the principles disclosed in the foregoing specification. For example, without departing from the principles disclosed in the foregoing specification, a plurality of features or preferred embodiments described herein may be combined, and the resulting technical solutions should be understood to belong to the content recorded herein. Unless otherwise specified in the claims, such changes are deemed to be included in the claims. Accordingly, the embodiments detailed herein are merely exemplary and are not intended to limit the scope of the present application, which is the full scope of the attached claims and any and all equivalents thereof.

Claims

1. A graphene premix, comprising: at least one dispersant having a sulfonyl imide moiety, the dispersant comprising an ionic liquid dispersant, the cation in the ionic liquid dispersant being a tributylmethylammonium cation, the ionic liquid dispersant having a fluorinated functional group, at least one glycidyl ether compound, the amount of the glycidyl ether compound being 75 wt % or more based on the total weight of the graphene premix, and At least one kind of graphene, wherein the graphene is 3-4 layers of graphene.

2. The graphene premix according to claim 1, wherein the ionic liquid type dispersant is tri-n-butylmethylammonium bis(trifluoromethylsulfonyl)imide.

3. The graphene premix according to any one of claims 1 to 2, wherein the molecular weight of the dispersant is 200-1000 g / mol.

4. The graphene premix according to any one of claims 1 to 2, wherein the glycidyl ether compound is selected from one or more of 2-ethylhexyl glycidyl ether, C10-C18 alkyl glycidyl ether, neopentyl glycol diglycidyl ether, butanediol diglycidyl ether, and butyl glycidyl ether.

5. The graphene premix according to any one of claims 1 to 2, wherein the graphene is one or more of intrinsic graphene, graphene oxide, and functionalized graphene, and the functionalized graphene has one or more of hydroxyl, carboxyl, carbonyl, amino, and thiol groups.

6. The graphene premix according to any one of claims 1 to 2, wherein the graphene premix comprises or consists of the following substances based on the total weight of the graphene premix: 0.5 to 20 wt % of a dispersant having a sulfonimide moiety, 75 to 98% by weight of a glycidyl ether compound, and 1 to 10 wt % graphene.

7. The graphene premix according to any one of claims 1 to 2, wherein the graphene premix does not contain an organic solvent other than the dispersant and the glycidyl ether compound, or the graphene premix contains no more than 3 wt % of an organic solvent other than the dispersant and the glycidyl ether compound based on the total weight of the graphene premix.

8. The graphene premix according to any one of claims 1 to 2, wherein the graphene premix is ​​in the form of a wet powder.

9. A coating composition comprising at least one film-forming resin and the graphene premix according to any one of claims 1 to 8.

10. The coating composition according to claim 9, wherein the weight ratio of the graphene in the graphene premix to the film-forming resin is 0.1:100 to 0.8:100, and / or The weight ratio of the dispersant in the graphene premix to the film-forming resin is 0.2:100 to 5:

100.

11. The coating composition according to claim 9 or 10, wherein the film-forming resin is one or more of bisphenol A epoxy resin, alicyclic epoxy resin, bisphenol F epoxy resin, novolac epoxy resin, alkyd resin, polyurethane, and acrylic resin.

12. The coating composition according to claim 9 or 10, wherein the film-forming resin is an acrylic resin.

13. The coating composition according to claim 9 or 10, wherein the coating composition is a two-component coating composition, the two-component coating composition further comprising a curing agent component, the curing agent component comprising at least one alicyclic amine curing agent.

14. A coated product comprising a substrate having at least one surface; and a coating composition or a cured coating thereof directly or indirectly applied on at least a portion of the at least one surface of the substrate, in, The coating composition is a coating composition comprising the graphene premix according to any one of claims 1 to 8 or a coating composition according to any one of claims 9 to 13.

15. The coated product according to claim 14, wherein The substrate is selected from metal, wood, wood composite, paper, plastic, fabric, ceramic, cement material or any combination thereof.

16. The coated product according to claim 14 or 15, wherein The coating has a uniform and smooth appearance and has a 10 6 Up to 10 10 Surface resistance of Ω.